Kepastian Hukum Kewajiban Saksi Instrumenter Dalam Menjaga Kerahasiaan Akta Autentik dan Akibat Hukumnya Terhadap Notaris - Diatmika, I Dewa Gede Agung Putra; Putu Laksmi Danyathi, Ayu (Acta Comitas : Jurnal Hukum Kenotariatan, 2023)
This research aims to examine the legal consequences of the non-regulation of the obligation of instrumental witnesses to maintain the confidentiality of authentic deeds against a notary and examine the formulation of arrangements for instrumental witness obligations in maintaining the confidentiality of the authentic deeds. This research uses normative legal research methods that use statutory and legal concept analysis approaches based on primary, secondary, and tertiary legal material sources, with the snowball method, as well as using descriptive analysis techniques and argumentative techniques. The results show that legal consequences of non-regulation of the obligation of instrumental witnesses to maintain the secrecy of authentic deeds to notaries is that notaries have the potential to be dragged into and subject to administrative sanctions, civil sanctions, and criminal sanctions due to the actions of instrumental witnesses who disclose secret deeds. Arrangements regarding the obligation of instrumental witnesses to maintain the confidentiality of the authentic deeds are important for legal certainty, provide protection to the parties involved in the deed and provide a sense of security to the notary. It is necessary to add arrangements for the obligations of deed witnesses/instrumental witnesses to maintain the confidentiality of the authentic deeds in the Explanation of Article 16 paragraph (1) letter f UUJN-P, as well as add to the understanding of deed witnesses/instrumental witnesses in the General Provisions Article 1 UUJN-P.